2012
DOI: 10.1111/maec.12011
|View full text |Cite
|
Sign up to set email alerts
|

Nematode diversity in different microhabitats in a mangrove region

Abstract: Mangroves are highly productive environments that play important ecological and socioeconomic roles; however, they have been impacted to different degrees in most countries worldwide. The knowledge of which organisms inhabit this environment and their ecological interactions is the first step towards its conservation. The natural variability of environmental factors in mangroves provides numerous niches available to different species. Meiofauna have patchy patterns of distribution that are related to the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 40 publications
1
28
1
Order By: Relevance
“…Coull 1999;Nicholas et al 1991). Terschellingia, in particular, can account for > 50% of all nematodes (Nicholas et al 1991), but several monhysterid genera can also be highly abundant (Pinto et al 2013). Alongi (1987) suggested that high levels of sediment- Litter from mangrove leaves is rapidly colonised by meiofauna, and there is a succession of different species related to the different stages of the decomposition process (Schrijvers et al 1995;Gee and Somerfield 1997;Somerfield et al 1998;Zhou 2001), supporting the idea that meiofauna taxa play a role in litter degradation (Gee and Somerfield 1997).…”
Section: Mangrove Meiofaunamentioning
confidence: 68%
See 3 more Smart Citations
“…Coull 1999;Nicholas et al 1991). Terschellingia, in particular, can account for > 50% of all nematodes (Nicholas et al 1991), but several monhysterid genera can also be highly abundant (Pinto et al 2013). Alongi (1987) suggested that high levels of sediment- Litter from mangrove leaves is rapidly colonised by meiofauna, and there is a succession of different species related to the different stages of the decomposition process (Schrijvers et al 1995;Gee and Somerfield 1997;Somerfield et al 1998;Zhou 2001), supporting the idea that meiofauna taxa play a role in litter degradation (Gee and Somerfield 1997).…”
Section: Mangrove Meiofaunamentioning
confidence: 68%
“…The use of mangrove leaf detritus as a food source by nematodes was confirmed using isotopic markers (Demopoulos et al 2007). The pneumatophores that are colonised by macroepibenthos, such as algae, sponges or barnacles, also promote the occurrence of meiofauna (Gwyther and Fairweather 2005;Pinto et al 2013). Dye (1983) recorded a greater abundance of nematodes in mangrove-associated sediments in comparison with adjacent estuarine mudflats, illustrating the importance of vegetation in providing food and habitat (Sheridan 1997).…”
Section: Mangrove Meiofaunamentioning
confidence: 99%
See 2 more Smart Citations
“…Meiofauna represent the most diversified group in the marine realm, encompassing 24 of the 35 animal phyla, as well as one important group of protists, the foraminifera (Giere 2009). Meiofauna are mostly found in and on soft sediments, but also on and among epilithic plants and other types of substrata (e.g., animal tubes; Pinto et al 2013). These small organisms can spend their complete life cycle without reaching sizes greater than 1 mm (permanent meiofauna), or be found in this size class for just a part of their life cycle (e.g., juveniles of macrofauna, referred to as temporary meiofauna; Hentschel and Jumars 1994).…”
Section: Introductionmentioning
confidence: 99%